Neurofilament light as a marker of neuro‐axonal injury and potential biomarker of disease progression in normal pressure hydrocephalus. (20th December 2022) - Taghdiri, Foad; Vasilevskaya, Anna; Anastassiadis, Chloe; Multani, Namita; Lang, Anthony E; Fasano, Alfonso; Tang‐Wai, David F.; Tartaglia, Carmela
Abstract: Background: The etiology of normal pressure hydrocephalus (NPH) is unknown. Patients worsen but the cause of the progression is unclear. A prognostic biomarker in NPH is required for selecting the best candidates for shunt surgery. Neurofilament‐light chain (NfL) is a marker of neuro‐axonal injury and is elevated in neurodegenerative disease, traumatic brain injury, stroke and encephalitis. The aim of this study was: (1) To compare cerebrospinal fluid (CSF) NfL of NPH patients with healthy controls (HC), and other neurodegenerative diseases: Alzheimer's disease (AD), and Frontotemporal lobar degeneration (FTLD); and (2) To evaluate CSF NfL levels as a potential biomarker of disease progression in NPH. Method: 108 patients with CSF analysis: (a) NPH group (39 patients): ventriculomegaly on MRI or CT, negative AD biomarkers, clinical symptoms of NPH, improvement in gait after removal of a large amount of CSF. 14 patients of the unshunted NPH group had a 1‐year follow‐up scan. EVANS index was calculated for these participants; (b) FTLD group (45 patients): 5 behavioural‐variant frontotemporal‐dementia, 19 corticobasal syndrome, 3 frontotemporal dementia with motor neuron disease, 13 progressive supranuclear palsy, 3 semantic‐variant primary progressive aphasia (PPA), and 2 non‐fluent PPA; (c) AD group (19 patients): CSF biomarkers and cognitive symptoms consistent with AD; and (d) HC group (5 participants): cognitively and functionally normal. Levels of NfL in CSF were measured using single molecule array (Simoa) technology. All statistical analyses were corrected for multiple comparisons and age. Result: NfL levels in patients with NPH were significantly higher than HC (1504.7±520 vs 702.5±170pg/ml, p < 0.001), and lower than FTLD group (1504.7±520 vs 3071.7±2830pg/ml, p=0.005). There was a trend for lower NfL in NPH compared to AD, (1504.7±520 vs 2305.4±1179.7pg/ml, p=0.056). There was a significant correlation between baseline NfL levels and increase in EVANS index (r=0.784, p=0.002) in the 14 NPH patients with longitudinal brain imaging. Conclusion: CSF NfL levels in NPH patients suggests there is neuro‐axonal injury but is lower than some other neurodegenerative diseases (i.e., FTLD and AD). NfL may be a biomarker for neuro‐axonal injury and disease progression in NPH.